Comparison of Water Quality in the Don River Pool, Russia, During 2011-2012 - AL-Ghizzi, Murooj Abbas Buhlool; Al- Mosawi, Aseel Kamil Mohammad. (Journal of Science in Medicine and Life, 2024)
The 2012 water quality analysis in the Don basin, a region in southern Russia, revealed a higher water content in 2012 compared to 2011, with the highest water consumption during spring floods and lowest during summer-autumn and winter low water periods. The basin's surface waters are highly diverse due to anthropogenic factors and physical and geographical conditions. Pollution sources include wastewater water from housing and communal services enterprises, chemical, petrochemical, metallurgical, agricultural, shipping, and small fleets. The water content of the Don River increased by 10-48% in 2012, accounting for 62-129% of the average multi-summer. The distribution of pollutants in the water from Donskoy to Azov remained unchanged, with sulfates being the largest and nitrite nitrogen being the smaller. Wastewater from various sources, such as Novomoskovsk City Vodokanal, remained a source of pollution. The level of water pollution in the Don River below Donskoy decreased by 3 times to 2 and 4 MPC, and by sulfates by 2 times to 2 MPC on average. The critical level of stability for water pollution in both sections was achieved for ammonium nitrogen, with average annual concentrations reaching 15-18 MPC. Downstream, the river water was characterized by the 3rd class of quality, with slight increases in water pollution in 9 out of 16 sites.